Geloofsontwikkeling: ’n Geloofsreis met roetemerkers - Anandie Greyling; Malan Nel (Verbum et Ecclesia)
Faith development: A journey through faith with route markers. The article explores the stage of adolescence and its characteristics, specifically concerning faith formation. It discusses the theological rationale for reaffirming one’s faith at various life transitions and rites of passage, focusing on how it can be implemented during adolescence.